157k views
3 votes
Solve for w. -2w + 2 = -4(w + 1) simplify your answer as much as possible

User Jvillian
by
5.1k points

1 Answer

5 votes

Answer:

The solution for “w” in -2w + 2 = -4(w + 1) is -3

Solution:

From question, given that -2w + 2 = -4(w + 1)

By multiplying the terms within the bracket with -4 in right side, the above equation becomes,

-2w + 2 = -4w -4

By moving the terms in right side to left side, the above equation becomes

-2w + 2 +4w + 4 = 0

Combining the like terms “-2w” and “4w” , we get

2w +2 + 4 = 0

2w + 6 = 0

2w = -6

w = -3

Hence the solution for “w” in -2w + 2 = -4(w + 1) is -3

User Nekman
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.